Model Pengembangan Bisnis BUMDes berdasarkan Pendekatan Sharing Economy dan Gig Economy: Studi di Wilayah Kabupaten Sumedang - Jaka Sudewa; Mohammad Fahreza (Coopetition : Jurnal Ilmiah Manajemen, 2021)
In an effort to encourage MSMEs, especially BUMDes Bhakti, the main village of Cilembu, it is necessary to develop a new business model, namely by utilizing opportunities by implementing the digital economy so that BUMDes business activities can operate properly and can follow business developments, so that the purpose of bumdes can be achieved, namely improving services to the community and empowering villages as autonomous regions with regard to productive efforts and improving business. emandirian and village capacity in strengthening the economy. This research aims to find out the potential and business barriers of BUMDes Bhakti Utama, knowing the efforts of BUMDes Bhakti Utama Cilembu in reviving bumdes business that is currently vacuum and to formulate a sharing economy and gig economy model so that the right business model is found for BUMDes, especially BUMDes Bhakti Utama that can be developed and operate in Cilembu Village so that it has a business development strategy that is in accordance with current conditions.  Thus, this study has a contribution, both in the development of theory and in the business practices of sharing economy and gig economy in efforts to empower the village economy. The method used in this study is qualitative descriptive analysis, which is presented in the form of drawings, tables and descriptions. This descriptive analysis method is processed based on elements of the Business Model Canvas and conducted an analysis of the potential and obstacles of businesses and then analyzed based on the sharing economy and gig economy approach to get the sharing economy and gig economy model. Furthermore, SWOT and PESTEL analysis is carried out to assess the extent to which new business models can be used so that alternative strategies / efforts can be formulated.